Metagenomic Binning Recovers a Transcriptionally Active Gammaproteobacterium Linking Methanotrophy to Partial Denitrification in an Anoxic Oxygen Minimum Zone - Padilla, Cory C.; Bertagnolli, Anthony D.; Bristow, Laura A.; Sarode, Neha; Glass, Jennifer B.; Thamdrup, Bo; Stewart, Frank J. (Frontiers in Marine Science, 2017)
Diverse planktonic microorganisms play a crucial role in mediating methane flux from the ocean to the atmosphere. The distribution and composition of the marine methanotroph community is determined partly by oxygen availability. The low oxygen conditions of oxygen minimum zones (OMZs) may select for methanotrophs that oxidize methane using inorganic nitrogen compounds (e.g., nitrate, nitrite) in place of oxygen. However, environmental evidence for methane-nitrogen linkages in OMZs remains sparse, as does our knowledge of the genomic content and metabolic capacity of organisms catalyzing OMZ methane oxidation. Here, binning of metagenome sequences from a coastal anoxic OMZ recovered the first near complete (95%) draft genome representing the methanotroph clade OPU3. Phylogenetic reconstruction of concatenated single copy marker genes confirmed the OPU3-like bacterium as a divergent member of the type Ia methanotrophs, with an estimated genome size half that of other sequenced taxa in this group. The proportional abundance of this bacterium peaked at 4% of the total microbial community at the top of the anoxic zone in areas of nitrite and nitrate availability but declining methane concentrations. Genes mediating dissimilatory nitrate and nitrite reduction were identified in the OPU3 genome, and transcribed in conjunction with key enzymes catalyzing methane oxidation to formaldehyde and the ribulose monophosphate (RuMP) pathway for formaldehyde assimilation, suggesting partial denitrification linked to methane oxidation. Together, these data provide the first field-based evidence for methanotrophic partial denitrification by the OPU3 cluster under anoxic conditions, supporting a role for OMZs as key sites in pelagic methane turnover.